2019
DOI: 10.1158/0008-5472.can-18-1544
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Phosphoribosyltransferase Acts as a Metabolic Gate for Mobilization of Myeloid-Derived Suppressor Cells

Abstract: Cancer induces alteration of hematopoiesis to fuel disease progression. We report that in tumor-bearing mice the macrophage colony-stimulating factor elevates the myeloid cell levels of nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in the NAD salvage pathway, which acts as negative regulator of the CXCR4 retention axis of hematopoietic cells in the bone marrow. NAMPT inhibits CXCR4 through a NAD/Sirtuin 1-mediated inactivation of HIF1a-driven CXCR4 gene transcription, leading to mobi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…Recently, it was demonstrated that iNAMPT acts also on myeloid-derived suppressor cells (MDSCs), where NAMPT blocks CXCR4 transcription, via a SIRT1/HIF-1α axis. The activation of this circuit, in turn, leads to MDSCs mobilization and enhances the production of nitric oxide, promoting immunosuppression (149).…”
Section: Enampt/enaprt In Myeloid Cells Function: the Role Of Tlr4mentioning
confidence: 99%
“…Recently, it was demonstrated that iNAMPT acts also on myeloid-derived suppressor cells (MDSCs), where NAMPT blocks CXCR4 transcription, via a SIRT1/HIF-1α axis. The activation of this circuit, in turn, leads to MDSCs mobilization and enhances the production of nitric oxide, promoting immunosuppression (149).…”
Section: Enampt/enaprt In Myeloid Cells Function: the Role Of Tlr4mentioning
confidence: 99%
“…Consequently, low CXCR4 resulted in mobilization of immature myeloid-derived suppressor cells (MDSCs), contributing to tumor immunosuppression. Importantly, pharmacologic inhibition of NAMPT resulted in a decrease in MDSC mobilization, reversing the immunosuppression and re-sensitizing tumor cells to immunotherapeutic agents in preclinical models (142).…”
Section: Immune Regulation Of Tumor Microenvironmentmentioning
confidence: 99%
“…In both type of diseases, the rapid myelopoiesis of myeloid cells at the BM is likely to be directed by several cytokines and transcription factors, among them interleukin-17A (IL-17A) ROR1C that induces IL-17A, G-CSF, GM-CSF, TNFa and others (2,4,6,14,37,38), whereas maintenance of the suppressive function is driven by several components that affect the activities of MDSC at the tumor site, including interaction with other cells, particularly T cells cytokines, chemokines, and transcription factors, and the effect of microRNA released from exosomes (39)(40)(41).…”
Section: The Two-stage Model Of Myeloid Cells Mobilization and Functionmentioning
confidence: 99%